Metals in mercury - Hirayama, C.; Galus, Zbigniew; Guminski, C. (Solubility data series, 1986)
The volume covers binary amalgams of all the metals, together with those of carbon, silicon and boron, a total of 76 systems. Complete literature coverage extends through 1983. The emphasis is on accurate, evaluated solubility data, but phase diagrams have been included where they have been defined, and will aid the reader in assigning the solid-liquid equilibrium. Tha data have been critically evaluated, and are classified as 'recommended' when independent determinations agree within experimental error. The data may also be used to compute thermodynamic properties of the binary components.